A landscape history of the Geul Valley: from a farmers’ Arcadia to a multifunctional landscape - Purmer, Michiel (JOURNAL OF LANDSCAPE ECOLOGY, 2019)
This article describes the role of Natuurmonumenten, a Dutch NGO for nature conservation, in the preservation of cultural landscapes. The case study is the traditional rural landscape of the Geul River, South Limburg, The Netherlands. The Geul Valley was recognized for its natural, geological and Arcadian beauty early in the 20th century. The nature conservationists took action in the early 20th century when industrialization already threatened the area. However, it was only after the Second World War, that nature conservation societies like Natuurmonumenten (Natural Monuments Society) bought parts of the Geul Valley in order to preserve the landscape. The Arcadian argument was strong: not only did Natuurmonumenten buy the flowery meadows, but also a castle, watermills, and ancient farmsteads. All within the paradigm of the traditional landscape. In the decades following the Second World War, however, the surrounding landscape changed dramatically due to increased tourism, intensive farming, growing population, land reallocations, etc. The contrast between the nature reserves and the surrounding parts of the valley grew. Now, in the early 21st century, new challenges arise: will nature management continue to strive for the preservation of the traditional landscape, or will nature development like rewilding take place? Climate change is an important issue and the sustainability of the management of the nature reserves is under discussion. This article uses the Landscape Biography method not only to describe the history of the management of the nature reserves of Natuurmonumenten in the Geul Valley, but also to look at the role of the cultural and natural heritage of this landscape in the transitions to come. The aesthetic aspect of the landscape also referred to like the beauty of the landscape, should play a role in the ongoing debate on the future of these landscapes.
Keywords: landscape biography; nature management; Arcadian landscape; landscape transformation; sustainability; landscape history